Optimal designs of multivariate synthetic |S| control chart based on median run length. Issue 6 (19th March 2017) - Lee, Ming Ha; Khoo, Michael B. C.
ABSTRACT: The multivariate synthetic generalized sample variance |S | (synthetic |S |) chart is a combination of the |S | sub-chart and the conforming run length sub-chart. A procedure for optimal designs of the synthetic |S | chart, based on the median run length (MRL), for both zero and steady-state modes are provided by minimizing the out-of-control MRL. The comparative results show that the synthetic |S | chart performs better than the standard |S | chart for detecting shifts in the covariance matrix of a multivariate normally distributed process, in terms of the MRL. An example is given to illustrate the operation of the synthetic |S | chart.